A Panel Cointegration Analysis of Pakistan’s Trade: Linkages with Regional and EU Economies - Khan, Aleena; Sattar, Abdul (Journal of Development and Social Sciences, 2024)
This research examines the trade potential between Pakistan and its 20 major trading partners from 1990 to 2020 using a gravity model of trade. Understanding bilateral trade dynamics is essential for Pakistan, given its economic ties with regional and global partners. The study analyzes various factors, including economic, geographic, and infrastructural elements that influence trade flows and assesses cross-sectional dependencies among countries. Findings indicate that stronger economies with larger populations and developed infrastructures promote higher trade volumes. Moreover, geographical distance significantly restricts trade potential, as evidenced by the absence of cross-sectional dependency, meaning trade shocks in one nation do not impact others directly. To boost regional trade, Pakistan should invest in infrastructure and lower barriers with neighboring countries. Additionally, strengthening trade agreements with the EU could diversify exports and reduce dependency on a limited number of partners. Future research should broaden the timeframe and consider alternative econometric techniques for a deeper understanding of trade dynamics.